2014
DOI: 10.1007/s00330-014-3480-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the contrast of white matter and grey matter in high-resolution phase difference enhanced imaging of human brain at 3.0 T

Abstract: • Phase difference enhanced (PADRE) imaging can yield diverse contrasts between tissues • The PADRE technique utilizes the inherent variety of magnetic susceptibilities • PADRE MR imaging provides better visualization of certain cerebral anatomy in vivo • PADRE imaging is able to delineate the stria of Gennari in the primary visual cortex • PADRE imaging is able to identify the two optic radiation layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…PADRE is a new phase-related imaging technique that can utilize any phase derived from both paramagnetic and diamagnetic substances. Previous studies of PADRE reported clear demonstration of normal structures, such as small fiber tracts of the brain stem ( 13 ), layers of the optic radiation, the stria of Gennari ( 16 , 17 ), gray-to-white matter interface or SWM ( 17 19 ) and the internal structures of the thalamus ( 14 ) with TEI. In addition, the relevance of PADRE findings to aging ( 49 ) and various pathological conditions including multiple system atrophy of the cerebellar type ( 13 ), Parkinson's disease ( 50 , 51 ), amyotrophic lateral sclerosis ( 15 ), multiple sclerosis ( 52 ) and Alzheimer's disease ( 53 ) has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…PADRE is a new phase-related imaging technique that can utilize any phase derived from both paramagnetic and diamagnetic substances. Previous studies of PADRE reported clear demonstration of normal structures, such as small fiber tracts of the brain stem ( 13 ), layers of the optic radiation, the stria of Gennari ( 16 , 17 ), gray-to-white matter interface or SWM ( 17 19 ) and the internal structures of the thalamus ( 14 ) with TEI. In addition, the relevance of PADRE findings to aging ( 49 ) and various pathological conditions including multiple system atrophy of the cerebellar type ( 13 ), Parkinson's disease ( 50 , 51 ), amyotrophic lateral sclerosis ( 15 ), multiple sclerosis ( 52 ) and Alzheimer's disease ( 53 ) has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A new phase-weighted MRI technique, phase difference-enhanced imaging (PADRE), uses the phase difference between the target and surrounding tissue to enhance the contrast of the target tissue. 10 , 11 Choosing the appropriate phase differences allows the variation in tissue contrast using single imaged magnetic resonance (MR) data. Some PADRE images yield a level of contrast that could not be realized with earlier phase techniques.…”
Section: Introductionmentioning
confidence: 99%